Genomic characterization and drug resistance of Bordetella pseudohinzii first isolated from wild niviventer - Jian Zhou; Sha Mao; Ying Liu; Tao Gu; Jingzhu Zhou; Fengming Chen; Yong Hu; Shijun Li (BMC Microbiology)
Abstract Background Niviventer, a rodent species widely distributed in Asian forests, serves as a significant reservoir for pathogens. Bordetella pseudohinzii(B. pseudohinzii), a recently identified Bordetella species with unclear pathogenic potential, poses challenges in species identification and understanding of its pathogenicity, its biological traits and antibiotic resistance are not well understood. Methods B. pseudohinzii(strains 21F10, 22F12, and 27F25) were isolated from lung tissue of wild niviventer rodents in Guizhou, China. Initial identification was performed using Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) and 16 S rRNA gene sequencing. A phylogenetic tree based on the 16 S rRNA gene sequences was constructed using the neighbor-joining method implemented in MEGA 11. Whole-genome sequencing (WGS) was conducted on all three strains, and strain 21F10 underwent hybrid assembly of second- and third-generation sequencing to achieve high-quality sequences. Average Nucleotide Identity (ANI) and digital DNA-DNA hybridization (dDDH) were used as gold standards for strain identification, with thresholds set at 95% and 70%, respectively. Gene annotation was performed using nine databases, including KEGG, VFDB, CARD, PHI, COG, and NR. Antimicrobial susceptibility testing was carried out using the drug-sensitive plate method. Results Initial MALDI-TOF MS identification misclassified the strains as B. avium and B. hinzii. However, PCR amplification of the 16 S rRNA gene (primers 27 F and 1492R) revealed that the strains were identified as B. hinzii (identity > 99%). Further analysis of the 16 S rRNA gene sequences obtained from WGS showed identities greater than 99% with both B. pseudohinzii and B. hinzii. Phylogenetic analysis of the 16 S rRNA gene sequences showed that the strains were closely related to B. hinzii, followed by B. pseudohinzii. Ultimately, the ANI values of all three strains with B. pseudohinzii were greater than 95%, and dDDH values exceeded 70%, confirming the strains as B. pseudohinzii. Strain 21F10 exhibited notable findings in terms of virulence factors and antibiotic resistance genes. Antimicrobial susceptibility testing revealed significant resistance to several cephalosporins (cefoxitin, cefuroxime, cefotaxime, cefazolin, and ceftiofur). The 16 S rRNA and WGS of strain 21F10 have been deposited in GenBank and Genome Sequence Archive (GSA)under accession numbers PQ881859 and CRA022358, respectively. Conclusion The first isolation of B. pseudohinzii from the lung tissue of wild niviventer was reported, and the limitations of traditional methods for identifying B. pseudohinzii were demonstrated. We highlight the superiority of WGS for accurate species identification. The findings reveal a complex pathogenic profile and notable antibiotic resistance, providing important insights for the future prevention and treatment of B. pseudohinzii infections in humans, as well as underscoring the need for monitoring B. pseudohinzii in rodent populations.